Managing and securing information through smart card: Government Multipurpose Smart Card (GMPC) / Nik Azmi Nik Omar - Nik Omar, Nik Azmi (2002)
A Smart Card is a standard credit card-sized plastic token within which a microchip has been embedded, hence making it effect a microcomputer. The chip is the engine room of the smart card, and indeed is what makes it 'smart'. MyKad or the Government Multipurpose Card (GMPC) is part of the Multimedia Super Corridor (MSC) flagship initiatives. The project commenced shortly after our Prime Minister unveiled his vision of a Multipurpose Card in 1996. Now After 5 years of intense research and development, it finally arrived at the conclusion of the pilot implementation phase of the project in which 2 Million cards will be issued. As of the end of 2001, MyKad will be in the hand of 1 Million citizens. As there was no other similar system deployed in other part of the world, this paper will give the overview of the GMPC project as well as MayKad, basic technology of the Smart Card, its benefits, the architecture and technology. Throughout the paper, the particular aspect of legal issue in implementation will be discuss briefly and it will also features the frame work for National Roll Out (NRO), challenge and risk and critical successful factor in the implementation of the project.